Refugee Exposure and Political Backlash: Poland during the Russia-Ukraine War - Joanna Clifton-Sprigg; Ines Homburg; Sunčica Vujić (Institute of Labor Economics (IZA), 2025)
This paper examines the impact of immigration on voting behaviour. Exploiting a unique natural experiment, we research parliamentary election results in Poland following the 2022 inflow of Ukrainian refugees. We exploit the variation in hosted refugees across Polish counties and utilise a shift-share instrument based on the past settlement of Ukrainian immigrants. We find increased support for far-right and right-wing (incumbent) political groups, at the expense of centre parties. There is important regional variation in this overall pattern. The more liberal areas in west Poland experienced political polarisation, with both far-right and left-wing parties gaining support. Furthermore, the rise in far-right support is particularly pronounced in rural counties, low wage counties, and those bordering Ukraine. The effects are driven by changing voter preferences, rather than election participation or natives' internal mobility, and are not rooted in adverse economic effects. Our findings show that exposure to refugees, even those with a similar background and favourable profile, can still be associated with natives' backlash.
Keywords: D72; D74; J15; O15; 330; Russia-Ukraine war; forced migration; refugee exposure; election results